Integrated design and control of multigeneration systems for building complexes - Fuentes-Cortés, Luis Fabián; Dowling, Alexander W.; Rubio-Maya, Carlos; Zavala, Víctor M.; Ponce-Ortega, José María (Energy (Oxford), 2016)
Building complexes have demands of electricity, cooling capacity for air conditioning, and sanitary hot water. These demands can be met efficiently using multigeneration systems. The design of a multigeneration system involves three integrated layers of decisions that include technology selection, equipment sizing and operational (control) policy design. In this work we cast this integrated design problem as a multi-objective mixed-integer nonlinear programming problem. The optimization formulation considers internal combustion engines, fuel cells, microturbines, Stirling engines, solar water heaters, and absorption chillers as technology options. The formulation also considers the sizing of a storage tank for hot water. Optimal operating policies are considered using daily scenarios of ambient temperature, solar radiation, fuel costs, electricity prices, and energy demands over an entire year. We compute compromise solutions that trade-off total annual costs, greenhouse gas emissions, and water consumptions. The method is demonstrated using real data for a Building complex with 420 households located on the Pacific Coast of Mexico. Our approach finds technologies that provide an optimal compromise between cost, emissions, and water consumption. In particular, we have found designs that reduce water consumption by 75% and emissions by 74% compared to the cost minimization case while increasing total cost by only 10%. •A multiobjective optimization model for designing domestic multigeneration systems is presented.•The model incorporates to satisfy domestic demands for electricity, hot water and cooling.•The model involves the simultaneous selection of technologies and operating conditions.•A case study for a residential complex of Mexico is presented.•Compensated solutions that trade-off the cost, emissions and used water are identify.